DIGITAL LITERACY INNOVATION FOR PUBLIC SERVICE PROVIDERS IN REMOTE, FRONTIER, AND OUTERMOST (3T) REGIONS - Rilit; Haryati, Eny; Widyawati (International Journal of Multidisciplinary Reseach, 2026)
This study aims to analyze the factors influencing digital literacy among public service providers in underdeveloped, frontier, and outermost (3T) areas, particularly in Lumbis District, Nunukan Regency, North Kalimantan. The method used is a qualitative approach with a case study design, where data is collected through in-depth interviews, observations, and documentation from public service providers directly involved in the use of digital technology in the area. The results show that public service providers in Lumbis District face significant challenges in terms of low digital literacy and limited technological infrastructure, which hinder the implementation of e-government and digital-based public service applications. The main factors identified are the mismatch between human resource competencies and the tasks they carry, as well as limited internet access that hinders the digitalization process. The contribution of this study is to provide insight into the need for technology-based training relevant to local needs and the importance of improving infrastructure to support the successful digitalization of public services in 3T areas. This study also suggests the importance of collaboration between the government, universities, and the private sector to accelerate digital transformation in underdeveloped areas.